Analisis Yuridis Tindak Pidana Penghinaan; Studi Kasus Berdasarkan Berita Acara Pemeriksaan dari Laporan Polisi NO: LP/B/163/V/2022, SPKT POLRES TTS POLDA NTT - Samara, Finsensius; Jehani, Marlioni T.; Tanehe, Indri P.A.; Meak, Doberto A.; Tari, Renata N.; Lawalu, Damianus Gonzales (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The crime of defamation is a type of crime that can damage a person's reputation and dignity. In the context of criminal law, defamation can be defined as an act intentionally committed to demean or defame a person. This study aims to legally analyze the crime of defamation based on police reports.The research method used was a case study, analyzing police reports related to defamation cases. The results indicate that defamation can occur in various ways, such as through words, writing, or actions. Furthermore, this study found that the elements of defamation, such as intentional, demeaning, and defamation, must be proven in the legal process.The conclusion of this study is that defamation can be prosecuted under the relevant articles of the Criminal Code, but careful analysis is necessary to ensure that the elements of defamation are met. Furthermore, this study emphasizes the importance of police reports in the legal process to prove defamation.